2005
DOI: 10.1159/000086903
|View full text |Cite
|
Sign up to set email alerts
|

Sperm studies in heterozygote inversion carriers: a review

Abstract: The risk of producing unbalanced gametes in heterozygous inversion carriers mostly depends on the occurrence of recombination events within the inverted segment. Recombination determines the possibility of producing chromosomes with duplications/deficiencies (pericentric inversions) or with duplications/deficiencies which furthermore appear as dicentric and acentric fragments (paracentric inversions). In this work, a general description of the close relationship between the occurrence of crossovers in pericent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 133 publications
4
50
0
3
Order By: Relevance
“…A second implication of our results is that the species from the yakuba complex can produce hybrids even though they carry multiple fixed inversions (Lemeunier & Ashburner, 1976). Inversions can cause hybrid sterility in chromosomal heterozygotes through the production of unbalanced gametes in a wide variety of organisms (Noor et al, 2001;Rieseberg, 2001;Anton et al, 2005). Sterility by structural misaligning of inversions is also a common condition in Drosophila (Naveira et al, 1984;Wasserman & Wasserman, 1992).…”
Section: Cross Gene Flowmentioning
confidence: 99%
“…A second implication of our results is that the species from the yakuba complex can produce hybrids even though they carry multiple fixed inversions (Lemeunier & Ashburner, 1976). Inversions can cause hybrid sterility in chromosomal heterozygotes through the production of unbalanced gametes in a wide variety of organisms (Noor et al, 2001;Rieseberg, 2001;Anton et al, 2005). Sterility by structural misaligning of inversions is also a common condition in Drosophila (Naveira et al, 1984;Wasserman & Wasserman, 1992).…”
Section: Cross Gene Flowmentioning
confidence: 99%
“…The rate of imbalanced recombinants seemed to be influenced by many factors, such as the chromosome involved, the region affected, the position of the breakpoints, or the size of the inverted segment [Anton et al 2005;Morel et al 2007]. The frequency of the recombinant gametes was plotted according to the relative length of the inverted segment of nine male carriers of a pericentric inversion of -chromosome 1.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, carriers of pericentric inversions do not show phenotypic alteration but they might have reproductive risks, such as the production of chromosomally imbalanced gametes and/or spermatogenetic failure caused by chromosome reorganization [Anton et al 2005;Ferfouri et al 2009]. During meiosis, the complete pairing of an inverted and its normal homologous chromosome requires the formation of an inversion loop, which may produce two abnormal gametes with both duplicated and deleted chromosome segments for regions distal to the inversion (duplication p/deletion q (dup p/del q) or deletion p/duplication q (del p/dup q)).…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies have mentioned that a significant level of unbalanced gametes would require a minimum inversion size of 100 Mbp and minimum segment proportion of 50.0% of the chromosome [23,24] for pericentric inversions (PEIs). Morel et al [24], suggested that significant number of recombinants are produced when the inverted segment size is >50.0% of the total length of the inverted chromosome.…”
Section: Discussionmentioning
confidence: 99%